PENDAMPINGAN PEMBUATAN SOAL KIMIA BERBASIS HIGH ORDER THINKING SKILL (HOTS) SESUAI TAKSONOMI BLOOM & ANBERSON-KRATHWOHL DI MAN BINJAI KOTA BINJAI - Nasution, Mutiara Agustina; Sutiani, Ani; Dibyantini, Ratu Evina; Sari, Dwy Puspita; Syafriani, Dewi; Sianturi, Yonaria Agustina; Nasution, Irma Yuliani (Jurnal Abdi Insani, 2024)
High Order Thinking Skills (HOTS) is a thinking process at a higher cognitive level, including the ability to solve problems, think creatively, think critically, argue and make decisions. This ability is expected to be possessed by students in the era of modernization and globalization of the 21st century. This achievement can occur if learning and assessment have implemented HOTS. However, in practice, many teachers still do not use HOTS questions to evaluate students in schools because of their low understanding of how to analyze and create HOTS questions according to Bloom's Taxonomy. This PkM activity aims to: 1) help partner groups increase insight and understanding regarding HOTS and its implementation in learning; 2) Helping partner groups improve skills in creating HOTS questions; and 3) meet the partners' needs for creating HOTS-based questions according to Bloom & Anderson-Krathwohl's Taxonomy independently. The methods used in this PKM are socialization of PKM activities, program preparation, implementation, mentoring and program monitoring and evaluation. The results that have been achieved are increasing partners' understanding of HOTS by 37.75%. This PKM activity can increase the knowledge and skills of madrasa stakeholders, especially teachers and staff. With independence in creating questions, teachers will better understand how questions can be connected to objectives and indicators, and in accordance with Bloom & Anderson-Krathwohl's Taxonomy and can improve teachers' ability to create questions independently, which will ultimately improve their skills in answering and analyze the questions.